Evidentiality, Inferentiality and Mirativity in the Modern Hindi - Sigorskiy, Alexander (Lingua Posnaniensis, 2010)
The questions of Evidentiality, Inferentiality and Mirativity in Hindi have not been thoroughly investigated so far. So the proposed description in no way can be exhaustive, and the results obtained are just preliminary. The approach adopted is functional, directed from function towards the modes of expression, because these categories in Hindi are rather semantic and functional, than structural and grammatical. The results indicate that all the three domains are semantically close to each other. All of them denote a source of new information, but formally they are very different. Three kinds of Evidentiality – reported evidentials, inferred evidentials and miratives – represent a semantic field with fuzzy structure. The only grammaticalized types of evidentials are inferred evidentials marked by moods. All evidentials are combined with different modal meanings. Some comparisons with other Indo-Aryan languages are made.